2011
DOI: 10.1158/1078-0432.ccr-11-0070
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2 Trial of Dasatinib in Patients with Advanced HER2-Positive and/or Hormone Receptor–Positive Breast Cancer

Abstract: Purpose: SRC-family kinases (SFK) are involved in numerous oncogenic signaling pathways. A phase 2 trial of dasatinib, a potent oral tyrosine kinase inhibitor of SFKs, was carried out in patients with human epidermal growth factor receptor 2-positive (HER2þ) and/or hormone receptor-positive (HRþ) advanced breast cancer.Experimental Design: Patients with measurable tumors and progression after chemotherapy and HER2 and/or HR-targeted agents in adjuvant or metastatic settings (maximum of two prior metastatic set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 31 publications
(37 reference statements)
1
56
0
1
Order By: Relevance
“…These results are in contrast to 2 recent phase II studies that also evaluated single-agent dasatinib for advanced breast cancer (19,20). In the first study, Finn and colleagues treated 44 patients with triple-negative MBC, 66% of whom had received prior therapy for advanced disease, and showed a clinical benefit rate (defined as partial response or stable disease lasting at least 16 weeks) of 9.3% (19).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These results are in contrast to 2 recent phase II studies that also evaluated single-agent dasatinib for advanced breast cancer (19,20). In the first study, Finn and colleagues treated 44 patients with triple-negative MBC, 66% of whom had received prior therapy for advanced disease, and showed a clinical benefit rate (defined as partial response or stable disease lasting at least 16 weeks) of 9.3% (19).…”
Section: Discussionmentioning
confidence: 80%
“…In the first study, Finn and colleagues treated 44 patients with triple-negative MBC, 66% of whom had received prior therapy for advanced disease, and showed a clinical benefit rate (defined as partial response or stable disease lasting at least 16 weeks) of 9.3% (19). In the second study, Mayer and colleagues treated 68 patients with HER2-amplified and/or HR-positive MBC, 93% of whom had received prior therapy for metastases, and showed a clinical benefit rate of 19%; interestingly, all patients who achieved some degree of disease control were HR-positive (20). Both studies showed that tolerability of dasatinib was better when the dose was reduced from 100 mg twice daily to 70 mg twice daily.…”
Section: Discussionmentioning
confidence: 99%
“…For specimens that passed QC, the median time from biopsy procedure to prediction results was 7 days (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Among the 30 patients who tested positive for at least one gene signature, 7 were positive for two different signatures (5 were double-positive for the DTI plus the cell line-derived sensitivity signature and 1 patient each for DTI plus SRC pathway and SRC pathway plus cell line-derived sensitivity signature).…”
Section: Biopsy Success Ratesmentioning
confidence: 99%
“…One study included patients with triple-negative disease and the other, patients with hormone receptor or Her-2-positive cancers. Both studies showed limited antitumor activity, with objective response rates of 4.7% and 5.6%, respectively (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…This may have resulted in decreased physiologic reserve as shown by the 44% frequency of ECOG PS of 0 compared with 60% of ECOG 0 patients in the aforementioned study [14]. Similar toxicities and short treatment times were observed in patients with advanced breast cancer treated with dasatinib following previous chemotherapy [18,19]. Recently reported results of the READY trial showed that the addition of dasatinib to docetaxel failed to prolong overall survival in patients with metastatic CRPC [20].…”
Section: Discussionmentioning
confidence: 82%